Market-based pricing for road freight transportation - A. A. Aksentev (Вестник университета, 2022)
The specifics of market pricing in the Russian road freight transport market by means of correlation and regression analysis have been studied. Statistically significant factors have been highlighted, and mathematical models have been constructed. The influence of fictitious variables (body type) that improve the quality of the calculated values has been noted. Regression equations useful for determining the average market value of tariffs have been drawn up, which, when compared to actual tariffs, may indicate the adequacy of freight transactions. The results of transport companies registered in the Krasnodar region have been considered. A differentiated approach has been justified, requiring enterprises to be divided into revenue growth groups in order to identify differences in profitability and its sustainability. The limitations and shortcomings of the mathematical model, which do not allow us to make an unambiguous conclusion about the unprofitable and low-margin nature of the industry, have been considered. Areas for future research have been suggested.